Firefighters and on-duty deaths from coronary heart disease: a case control study - Soteriades Elpidoforos S; Kales Stefanos N; Christoudias Stavros G; Christiani David C (BMC, 2003)
Abstract Background Coronary heart disease (CHD) is responsible for 45% of on-duty deaths among United States firefighters. We sought to identify occupational and personal risk factors associated with on-duty CHD death. Methods We performed a case-control study, selecting 52 male firefighters whose CHD deaths were investigated by the National Institute for Occupational Safety and Health. We selected two control populations: 51 male firefighters who died of on-duty trauma; and 310 male firefighters examined in 1996/1997, whose vital status and continued professional activity were re-documented in 1998. Results The circadian pattern of CHD deaths was associated with emergency response calls: 77% of CHD deaths and 61% of emergency dispatches occurred between noon and midnight. Compared to non-emergency duties, fire suppression (OR = 64.1, 95% CI 7.4-556); training (OR = 7.6, 95% CI 1.8-31.3) and alarm response (OR = 5.6, 95% CI 1.1-28.8) carried significantly higher relative risks of CHD death. Compared to the active firefighters, the CHD victims had a significantly higher prevalence of cardiovascular risk factors in multivariate regression models: age ≥ 45 years (OR 6.5, 95% CI 2.6-15.9), current smoking (OR 7.0, 95% CI 2.8-17.4), hypertension (OR 4.7, 95% CI 2.0-11.1), and a prior diagnosis of arterial-occlusive disease (OR 15.6, 95% CI 3.5-68.6). Conclusions Our findings strongly support that most on-duty CHD fatalities are work-precipitated and occur in firefighters with underlying CHD. Improved fitness promotion, medical screening and medical management could prevent many of these premature deaths.